Endoscopic treatment of spinal trauma at the thoracolumbar junction - Beisse, Rudolf (Medknow Publications, 2007)
Attempts of treating unstable fractures of the thoracolumbar junction by posterior reduction and fixation alone often result in a significant loss of correction, especially in lesions where a severe destruction of the vertebral body and the intervertebral disc is present. The conventional open approaches like classic thoraco-phreno-lumbotomy produces additional iatrogenic trauma at the lateral chest and abdominal wall which not rarely leads to intercostal neuralgia, as well as post-thoracotomy syndromes. The endoscopic trans-diaphragmatic approach described below opens up the whole thoracolumbar junction to a minimally invasive procedure allowing one to perform all the procedures needed for a full reconstruction of the anterior column of the spine like corpectomy, decompression, vertebral body replacement and anterior plating. The key to address also the subdiaphragmal and retroperitoneal section of the thoracolumbar junction is a partial detachment of the diaphragm which runs along the attachment at the spine and the ribs. The technique was published first in 1998 and has been used now in 650 endoscopic procedures at the thoracolumbar junction out of a total of more than 1300 thoracoscopic operations of the spine in the BG Unfallklinik Murnau, Germany since 1996.